The Role of Physical Activity in the Prevention and Management of Chronic Low Back Pain: A Health Education and Sport Science Perspective - Sieradzka, Izabela; Wajda , Katarzyna; Słowik , Justyna (Quality in Sport, 2026)
Introduction: Chronic low back pain (CLBP) remains a critical challenge for public health and physical culture, significantly impacting quality of life and generating substantial healthcare costs. In the context of health education, a sedentary lifestyle is identified as a primary modifiable risk factor that requires targeted movement-based interventions. Objective: This review aims to synthesize current evidence on the role of physical activity in both the prevention and management of CLBP. Particular emphasis is placed on the physiological mechanisms of exercise and the pedagogical effectiveness of various sports-related interventions. Methods and Materials: A narrative review was conducted based on literature published between 2006 and 2026. The analysis included cohort studies, randomized controlled trials (RCTs), and meta-analyses focusing on diverse modalities, including core stabilization, aerobic training, Pilates, yoga, and aquatic exercises. Results: Regular engagement in physical activity effectively reduces the risk of CLBP occurrence and recurrence by enhancing muscular endurance, spinal stability, and neurobiological pain modulation. Notably, the review finds that interventions integrating physical exercise with health education (e.g., postural awareness and movement ergonomics) yield superior outcomes in reducing kinesiophobia (fear of movement) and functional disability compared to exercise alone. Conclusions: Physical activity should be promoted as a primary health-seeking behavior in CLBP care. To optimize public health outcomes, individually tailored exercise programs should be integrated with educational strategies, positioning sport and physical culture as essential components of modern spinal health management.